Preparation of superhydrophobic nanocomposite fiber membranes by electrospinning poly(vinylidene fluoride)/silane coupling agent modified SiO2 nanoparticles. Issue 13 (28th November 2016) - Sun, Haixiang; Xu, Yanyan; Zhou, Yingying; Gao, Wen; Zhao, Haoru; Wang, Wenguang
ABSTRACT: Superhydrophobic nanocomposite fiber membranes were prepared by blend electrospinning of poly(vinylidene fluoride) (PVDF) mixed with silane coupling agent modified SiO2 nanoparticles. The nanoparticles were prepared by the sol–gel method, and the average particle diameter was measured by dynamic light scattering (DLS) and transmission electron microscopy (TEM). The effects of the type of silane coupling agent, such as n ‐octyltriethoxysilane, vinyltrimethoxysilane (A‐171), and vinyltriethoxysilane (A‐151), and the mass ratio of the modified silica particles and PVDF on the surface wettability of the composite fiber membrane were investigated. The results indicated that the incorporation of silane coupling agent modified silica particles into the PVDF membrane increased the roughness of the surface and formed micro/nano dual‐scale structure compared to the pristine PVDF membrane, which was responsible for the superhydrophobicity and self‐cleaning property of the nanocomposite fiber membranes. The value of water contact angle (CA) increased with the increase of the content of modified SiO2 nanoparticles in the nanocomposite membrane, ranging from 149.8° to 160.1° as the mass ratio of modified 170 nm SiO2 with PVDF matrix increased from 0.5:1 to 5:1, indicating the membrane possesses a superhydrophobic surface. © 2016 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 44501. Abstract :